Use of density sorting for the selection of aromatic grape berries with different volatile profile. (15th March 2019) - Pollon, Matteo; Torchio, Fabrizio; Giacosa, Simone; Segade, Susana Río; Rolle, Luca
Highlights: Four grape varieties were analyzed for their volatile profile after density sorting. Changes in free volatile compounds were variety-dependent, with few common trends. Little differences in total glycosylated content among berries sorted by flotation. Limited effectiveness of density sorting to obtain different aroma profiles. Abstract: The aim of the study was to investigate the application of berry density sorting as a tool for the selection of grapes with different volatile and precursor profiles. The study was carried out on Moscato giallo, Malvasia di Schierano, Malvasia nera lunga, and Brachetto aromatic grape varieties. Free and glycosidically-bound terpene compounds including linalool, geraniol, nerol, citronellol, and terpineol, as well as lipoxygenases activity-derived compounds, were evaluated using head space-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) in density sorted berries (1075–1119 kg m −3 ). Total free terpenes changed with the berry density, while no significant changes were found in total glycosylated compounds, except for Malvasia nera lunga grapes where nerol, linalool, and geraniol contributed strongly to the increase of total contents with increasing berry density. Given that these variations were strongly variety-dependent, the possible use of density sorting equipment in winery for this aim may be less effective.